Consideration of Positive and Negative Impacts of Smart Tourism on Destination Branding, Case of Uzbekistan - Yakubova, Ms. Yulduz (GREEN ECONOMY AND DEVELOPMENT, 2023)
The thesis below attempts to raise the awareness as well as draw the discussion on both positive and negative effects that Smart tourism practices may carry in general and for the case of Uzbekistan. It draws the attention on some of the possible impacts the practices may carry on the destination branding